The Role of Natural Theology and Its Sources in the Anti-Eunomian Discourse Concerning Comprehensibility of God - Karolina Kochańczyk-Bonińska (The Francis de Sales Scientific Society (TNFS.PL), 2017)
Basil and Gregory criticized dialectics on the grounds that it tries to usurp the truths that could only be known through Revelation. Nevertheless, the Church Fathers developed natural theology in which they deliberately used arguments based on sensual cognition, human logic or philosophical tradition, and especially on common notions. Although their terminology is often inconsistent and they use technical terms interchangeably, the context provides us with clear ideas of their theses. We should admit that as, far as dialectics and philosophy were concerned, the orthodox authors despite many reservations used all possible methods to reach the truth. They favoured the Scripture and the Tradition, but also respected such sources as sensual perception, human logic or common notions and preconceptions.